2017
DOI: 10.1093/cid/cix641
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Case Finding With Combined Rapid Point-of-Care Assays (Xpert MTB/RIF and Determine TB LAM) in HIV-Positive Individuals Starting Antiretroviral Therapy in Mozambique

Abstract: The prevalence of tuberculosis among Mozambican HIV-positive patients starting antiretroviral therapy was 10%, with limited rifampicin resistance. Use of combined point-of-care tests increased case finding, with a short time to treatment. Interventions are needed to remove logistical barriers and prevent presentation in very advanced HIV/tuberculosis disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…Some studies of pre-ART patients have found LAM useful for diagnosing TB. 7,8,11,13 In our study, half of the LAMpositive patients were on ART, and ART-naive patients did not have a higher likelihood of being LAM positive than those on ART, suggesting systematic LAM's utility for diagnosing TB in severely immunosuppressed patients, regardless of their ART status. A South African study of patients under HIV care found very low LAM positivity, 6 although high degrees of immunosuppression in our study population (median CD4 was 31 cells/μL compared with 111 cells/μL in Hanifa et al study) may partially explain this difference.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Some studies of pre-ART patients have found LAM useful for diagnosing TB. 7,8,11,13 In our study, half of the LAMpositive patients were on ART, and ART-naive patients did not have a higher likelihood of being LAM positive than those on ART, suggesting systematic LAM's utility for diagnosing TB in severely immunosuppressed patients, regardless of their ART status. A South African study of patients under HIV care found very low LAM positivity, 6 although high degrees of immunosuppression in our study population (median CD4 was 31 cells/μL compared with 111 cells/μL in Hanifa et al study) may partially explain this difference.…”
mentioning
confidence: 53%
“…4,5 Diagnostic accuracy studies of LAM for TB diagnosis of HIV-positive patients irrespective of signs and symptoms have provided inconsistent results. [6][7][8][9][10][11][12][13] In a recent systematic review, the sensitivity and specificity of LAM in outpatients, irrespective of their TB symptoms, was 31% and 95%, respectively, 14 and the just published WHO TB-LAM revised guidelines recommend the use of LAM in HIV-positive patients with CD4 count les than 100 cells/μL, irrespective of signs and symptoms of TB 15 We assessed LAM results and TB diagnosis in ambulatory, severely immunosuppressed HIV patients, who had LAM systematically performed at new or regular HIV consultations. We also assessed the association between LAM results and mortality at 6 months.…”
mentioning
confidence: 99%
“…In a previous study [ 10 ], a TB-diagnosis algorithm based on combined rapid POC assays was evaluated in 972 HIV+ patients in Mozambique. In the present study, to evaluate the cost-effectiveness of the different screening protocols, a simulation was performed on a sample of 1,000 HIV+ patients, with an average age of 35 years at the time of the positive HIV test, as in the previous study.…”
Section: Methodsmentioning
confidence: 99%
“…True-positive-, true-negative-, false-positive- and false-negative-cases were derived on the basis of sensitivity and specificity of tests. Sensitivity and specificity of 4SS was considered 77.5% and 70.4% respectively as described by Floridia et al [ 10 ]. This specificity value differed from that reported by the WHO of 50% [ 1 ], but data regarding performance of 4SS is widely heterogeneous among studies [ 14 16 ]; individual performance assessments for SMEAR, MTB/RIF and LF-LAM were derived from previous studies or international guidelines where all test were compared with gold standard culture tests [ 17 – 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation